Covalent Chemical Tools for Profiling Post-Translational Modifications - Emenike, Benjamin; Nwajiobi, Ogonna; Raj, Monika (Frontiers in Chemistry, 2022)
Nature increases the functional diversity of the proteome through posttranslational modifications (PTMs); a process that involves the proteolytic processing or catalytic attachment of diverse functional groups onto proteins. These modifications modulate a host of biological activities and responses. Consequently, anomalous PTMs often correlate to a host of diseases, hence there is a need to detect these transformations, both qualitatively and quantitatively. One technique that has gained traction is the use of robust chemical strategies to label different PTMs. By utilizing the intrinsic chemical reactivity of the different chemical groups on the target amino acid residues, this strategy can facilitate the delineation of the overarching and inclusionary roles of these different modifications. Herein, we will discuss the current state of the art in PTM analysis, with a direct focus on covalent chemical methods used for detecting them.